Successful aging scale: Validity and reliability study - YÜKSEL, MÜGE (My University, 2022)
The purpose of this research is to develop a successful aging scale specific to Turkey. This research was carried out on two different study groups for exploratory and confirmatory factor analysis studies. The study group formed for exploratory factor analysis consists of 521, and the group for confirmatory factor analysis consists of 243 elderly individuals.By the analyzes carried out, the KMO value of the Successful Aging Scale was found to be .97; validity and reliability analyzes were continued. It was observed that the 19-item SAS with item loads varying between .74 and .84 explained 61.42% of the total variance. After the exploratory factor analysis studies of the SAS, the confirmatory factor analysis studies were started and after the two modifications, the model fit indices were found at an acceptable level (χ2 / df = 2.24, RMSEA = .069, CFI = .922, TLI = .911, SRMR =. .067). In order to determine the criterion-based validity of the SAS, Successful Aging Scale and the Aging In-Situ Scale were used. As a result of the analysis, it was seen that the SAS showed a moderate meaningful relationship with both scales. The Cronbach alpha internal consistency coefficient of the total score of the SAS was calculated as .96 in the first study group and .90 in the second study group.
Keywords: Successful aging; scale; elder